Fatty Acid Profile in Plasma and Red Blood Cells in Chronic Fatigue Syndrome Patients - Miranda, Gemma; Arranz, Laura; Ventura, Josep L; Rafecas, Magda; Segura, Ramon; Javierre, Casimiro (Journal of Pharmacy and Nutrition Sciences, 2011)
Chronic Fatigue Syndrome is an illness of unknown aetiology that has been associated with abnormalities in essential fatty acid metabolism, however this still remains unclear. We have compared the fatty acid profile in plasma and red blood cells and their dietary intake between a group of 20 patients diagnosed with CFS (18 women and 2 men) and 20 aged- sex- diet- low activity- matched controls. Compared to the controls, CFS patients show a decrease in the proportion of linoleic acid (t: 2.137, p: 0.039) and an increase in that of stearic acid (t: 2.602, p: 0.013) in plasma, however such differences have not been observed in the fatty acid profile of red blood cells. In these cases, no direct relationship has been observed between the dietary intake and fatty acid profile. Therefore, these results do not give support that long-chain polyunsaturated fatty acids may contribute in the better course of the pathology.